Odpowiedzi

2010-02-23T20:58:11+01:00
6(x-4)-2=6x-24-2=6x-26
2(x+1)-3(x-1)=2x+2-3x+3=5x+5
-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
2(3a+b)-2(a-b)= 6a+2b-2a+2b=4a+4b
5a(a-3)-3a(a-5)= 5a²-15a-3a²+15a= 2a²
tto jest na pewno dobrze??????????????????????????
Najlepsza Odpowiedź!
2010-02-23T20:59:43+01:00
6(x-4)-2=6x-26
2(x+1)-3(x-1)=2x+2-3x+3=-x+5
-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
5a(a-3)-3a(a-5)=5a^2-15a-3a^2+15a=2a^2

* ^ - do potęgi :)